Pengaruh Lingkungan Bisnis, Orientasi Pasar, Karakteristik Kewirausahaan terhadap Kinerja UMKM Keripik di Kabupaten Pasuruan - Habibah (Journal of Economic, Management and Entrepreneurship, 2023)
This study aims to determine the effect of the Business Environment, Market Orientation, Entrepreneurship Characteristics on the Performance of SME Chips in Pasuruan Regency. The population in this study is the perpetrators of SME Chips in the Pasuruan Regency area as many as 119 SME Chips. The research method used was a survey method. The sampling technique uses Saturated Sample Technique which uses all the population of 119 MSMEs. Data analysis techniques used multiple regression analysis. The results obtained from this study indicate that the variable Business Environment, Market Orientation, Entrepreneurial Characteristics have a significant positive effect on the Performance of SME Chips in Pasuruan Regency with a test value of X1 3,546> t table 1,984 with a significant value of 0.001 <0.05, tcount X2 5.986> ttable 1.984 with a significant value of 0.000 <0.05, tcount X3 1.997> t table 1.984 with a significant value of 0.048 <0.05.